Analisis Aspek Keperilakuan Terhadap Penerapan Sistem Akuntansi Persediaan Pada Dinas PUPRD Provinsi Sulut - Kiet Tumiwa; Ivoletti Walukow; Regina M. Losu (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The purpose of this research was to determine the effect of behavioral aspects of attitudes, perceptions, and emotions on the application of the inventory accounting system at the Department of Public Works and Spatial Planning of North Sulawesi Province. The method used in this research is a quantitative method with multiple linear regression approach. The population of this research is the employees of the Department of Public Works and Regional Spatial Planning of the Province of North Sulawesi. While the research sample used by the researcher was 14 respondents. The results showed that the behavioral aspect of the attitude had no effect with a value of 0.078 on the implementation of the inventory accounting system. The behavioral aspect of perception has no effect with a value of 0.555 on the application of the inventory accounting system. Aspects of emotional behavior have no effect with a value of 0.714 on the implementation of the inventory accounting system. This is because the Department of Public Works and Spatial Planning of the Province of North Sulawesi has a good culture where this culture is the basis for employees to work based on standard operating procedures that have been set so that there is no opportunity to raise debates in aspects of behavior, attitudes, perceptions and emotions. The R Square value is 0.312 or 31.2%. This figure shows that the contribution of the behavioral aspects of attitudes, perceptions and emotions to explain the variables of the application of the inventory accounting system.